Semantic schema matching approaches: a review - Hossain, Jafreen; Mohd. Sani, Nor Fazlida; Affendey, Lilly Suriani; Ishak, Iskandar; Kasmiran, Khairul Azhar (Asian Research Publication Network, 2014)
An extensive review of the existing research work in the field of schema matching uncovers the significance of semantics in this subject. It is beyond doubt that both structural and semantics aspect of schema matching have been the topic of research for many years and there are strong references available for both. However, an in-depth analysis of all the available approaches suggests there are further scopes for improvement in the field of semantic schema matching. Normalization and lexical annotation methods using WordNet have been proposed in several studies, but the level of matching accuracy in those studies have not yet reached a point that can encourage full automation of schema matching in commercial use. This paper lists out several possible future work based on the existing limitations.